P16 An interdisciplinary study of historical and epidemiological transitions in urban caribbean foodscapes: understanding the past to enhance future nutrition strategies. (3rd September 2019) - Guell, C; Altink, H; Moore, M; McMorris, M; Morrissey, K; Smith, M; Unwin, N; Williams, A; Govia, I
Abstract : Background: Healthy environments need to be created that enable easy access to healthy and nutritious food. Complex and expanding urbanisation has had deleterious effects on the diet and health of city dwellers; yet urban planning offers a potential mechanism for public health strategies. To inform such policy efforts in the Caribbean, we conducted a cross-disciplinary study to understand historical and epidemiological transformations in Kingston, Jamaica. With this case study, we aimed to develop methods and conceptual tools for investigating the historical social, political and economic contexts that have shaped contemporary foodscapes and can inform future nutrition strategies. Methods: Caribbean historians analysed principally online Jamaican newspaper archives to examine changes in food availability, affordability and consumption, and public discourses around eating, particularly fast food and other types of unhealthy food, from 1945 to present. Public health researchers undertook a scoping review to map available regional health survey databases for local nutrition and related health data, to examine major epidemiological trends in nutrition for the same time frame and assess its impact on non-communicable diseases. Geographical information scientists mapped the health and historical data to produce an interactive map of the evolution of Kingston's foodscape. Results: Preliminary historical findings include: the increasing popularisation of commercial, more quickly prepared meals between the 1950s and 1970s; a national campaign to promote locally produced food crops in the diet to address food scarcity in the late 1970s; and the proliferation of United States fast food chains in Kingston in the 1980s. The health data review found thirteen relevant health or nutrition surveys on malnutrition including childhood stunting rates, nutrient deficiency and obesity rates. Few predate the 1980s and many only offer national (versus city level) data. Annual health and demographic reports pre- and post-independence in 1962 might be able to fill data gaps. For the geographical information systems map, we had to identify relevant historical address points, as well as identify and digitalise historical maps from 1945 onwards onto which data can be layered. Conclusion: Structural approaches to public health require us to expand the scope of transdisciplinary research and build the methodological capacity to make 'non-traditional' connections. In this case study of the health history of a major Caribbean urban space, while not claiming causal relationships between historic and health trends, we suggest the important role that natural events, international and local policies, and advertising driven economies play in the production of 'unhealthy' foodscapes over time. This project was funded by the UK Medical Research Council – Arts and Humanities Research Council GCRF Global Public Health Partnership Award [Grant number: MR/R024324/1].